The Effect of Blood Sugar Fasting Levels on Diabetic Dyslipidemia - Raheela Yasmin, Aashi Ahmed, Ambreen Javed, Maleha Asim, Rabbia Shabbir, Shahida Mushtaq, Faiza Irshad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetic dyslipidemia is a group of lipoprotein defects described by raised triglycerides, elevated low density lipoprotein and reduced levels of high density lipoprotein. Objective: To assess the effect of blood sugar fasting levels on individual lipoproteins. Study design: Cross-sectional study Place and duration of study: Fauji Foundation Hospital Rawalpindi & POF Hospital Wah Cantt from 1st February 2014 to 31st July 2014. Methodology: Fifty patients with age from 30 to 70 years were enrolled. Patients' body mass index was calculated. Serum cholesterol, high density lipoprotein and triglyceride levels were estimated by enzymatic colorimetric kit. Low density lipoprotein was calculated by Friedewald equation. Results: The mean blood sugar fasting level was 204.050±87.0755. The P-value of low density lipoproteins to blood sugar fasting and cholesterol to high density lipoprotein ratio blood sugar fasting were significant i.e. 0.03 and<0.001 respectively. Conclusion: Dyslipidemia worsened with uncontrolled blood sugar fasting. Elevated low density lipoprotein and cholesterol to high density lipoprotein ratio was observed. Keywords: